Different Impacts of COVID-19 on Quality of Therapy, Psychological Condition, and Work Life Among Occupational Therapists in Physical and Mental Health Fields - Sawamura, Daisuke; Ito, Ayahito; Miyaguchi, Hideki; Nakamura, Haruki; Ishioka, Toshiyuki (Frontiers in Public Health, 2022)
Background: The negative impacts of the coronavirus disease 2019 (COVID-19) pandemic have worsened the quality of therapy, psychological condition, and work life of second-line healthcare workers and occupational therapists (OTs). However, no study has investigated whether the impact of COVID-19 varies among OTs working in different fields. This study aimed to investigate the differences on the impact of COVID-19 between OTs in the physical and mental health fields. Methods: A cross-sectional online survey was conducted in Japan between January 20 and January 25, 2021. A total of 4,418 registered OTs who were members of the Japanese Association of Occupational Therapists volunteered for this study. After screening using the exclusion criteria, 1,383 participants were classified into two groups based on their field (mental health and physical health), and their quality of therapy, psychological condition, and work life were analyzed. Results: OTs in the mental health field showed a greater decrease in therapy quality and increase in workload and a lower rate of decrease in working hours than those in the physical health field. In the multinomial logistic regression analysis, decreased and increased therapy quality and decreased therapy quality were significantly associated with depression in the physical health field, and decreased therapy quality was associated with insomnia in the mental health field. Furthermore, insomnia and anxiety were commonly associated with increased workload and working hours, respectively, in both fields, whereas anxiety and depression were associated with increased workload only in the physical health field. Conclusions: These results demonstrate that COVID-19 differently impacted quality of treatment, workload, work time, and psychological condition in the physical and mental health fields; moreover, the relationships among these are different in these two fields. These results highlight the importance of investigating the field-specific negative impacts of COVID-19 on OTs and may provide helpful information for devising tailored and effective prevention and intervention strategies to address these challenges.